Microplastic interactions with North Atlantic mesopelagic fish. (23rd December 2015) - Lusher, Amy L.; O'Donnell, Ciaran; Officer, Rick; O'Connor, Ian
Abstract: Microplastics in the marine environment are well documented, and interactions with marine biota have been described worldwide. However, interactions with vertically migrating fish are poorly understood. The diel vertical migration of mesopelagic fish represents one, if not the largest, vertical migration of biomass on the planet, and is thus an important link between the euphotic zone, transporting carbon and other nutrients to global deep sea communities. Knowledge of how mesopelagic fish interact and distribute plastic as a marine contaminant is required as these populations have been identified as a potential global industrial fishery for fishmeal production. Ingestion of microplastic by mesopelagic fish in the Northeast Atlantic was studied. Approximately 11% of the 761 fish examined had microplastics present in their digestive tracts. No clear difference in ingestion frequency was identified between species, location, migration behaviour, or time of capture. While ingesting microplastic may not negatively impact individual mesopelagic fish, the movement of mesopelagic fish from the euphotic zone to deeper waters could mediate transfer of microplastics to otherwise unexposed species and regions of the world's oceans.